DIFFERENTIAL METHOD OF QUALITY CONTROL OF PHYSICO-MECHANICAL CHARACTERISTICS OF KNITTED FABRIC FOR BATHING SUIT - RIABCHYKOV, Mykola; NAZARCHUK, Liudmyla; STYTSIUK, Viktoriia; TKACHUK, Oksana; KAHAN, Oksana (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The actuality of the introduction of textile materials with the content of nanopowders based on oxides of divalent and trivalent iron has been proven. The main directions of implementation of such materials into real practical results are shown. The algorithm for the synthesis of magnetic nanomaterials was developed. Adhesion properties of magnetic nanopowders to textile fibers are determined. It is shown that exposure for 5 - 7 days ensures almost absolute adhesive resistance and provides a combination of textile properties with magnetic nanopowders. Bacteriostatic properties of nanomagnetic textile materials were determined. For this purpose, the growth dynamics of mold fungi was determined. It is shown that the content of nanomagnetite significantly suppresses the growth of mold infections. The magnetic properties of textile materials are described, the possibilities of their introduction into elements of smart clothing, medical and protective materials are determined. Magnetic technologies in medicine, compression elements of clothing can be provided with the help of magnetic textile materials. The magnetic effects of such materials make it possible to create elements of clothing with a change in geometry. This determines the possibility of using such materials for smart clothes with new effects. The possibilities of creating magnetic nanomaterials with given structural characteristics have been proven. The addition of nanopowders reduces the size dispersion of structural elements, reduces their size, and increases density. This effect allows ensuring the specified transfer characteristics of textile materials, which provide the necessary parameters of heat transfer and mass transfer. The possibilities of using magnetic textile materials against electromagnetic radiation are shown. The structure of directions for the use of magnetic textile materials for medical and protective products, as well as for promising elements of smart clothing, has been developed.
Keywords: magnetic textile materials; nanocomponents; smart clothing; medical textiles